The effects of sorghum fractions on pet food extrusion, digestibility and antioxidant capacity in dogs - Alvarenga, Isabella Corsato (Kansas State University, 2016)
Novel ingredients fuel growth in the pet food market. Sorghum grain is a promising ingredient source. It grows in semi-arid regions and the pericarp is rich in phenolic compounds that are well-known antioxidants. The objectives were to determine the impact of milling sorghum on yield and composition of the various fractions, their impact on diet extrusion, and nutrient utilization when fed to dogs. Sorghum milling yields were 68.3% flour, 27.2% mill-feed, and 1.25% germ. Four nutritionally similar dog diets were extruded containing whole sorghum (WSD), sorghum flour (FLD), sorghum mill-feed (MFD), or a control diet (CON) with an equal proportion of corn, wheat and rice. The MFD had the highest (P < 0.05) bulk density and was 1.37-fold heavier than FLD. The FLD had a sectional expansion index (SEI) of 1.92 and 1.35-fold more than MFD and WSD. The FLD and MFD had the hardest kibbles (P < 0.05). Twelve Beagle dogs were fed the experimental diets in a 4 period replicated Latin square design with 9 d adaptation and 5 d total fecal collection (TFC). Fecal output was also estimated using acid insoluble ash (AIA), Cr₂O₃ and TiO₂. Plasma antioxidant activity was measured by oxygen radical absorbance capacity (ORAC) method. Fecal scores were highest (P < 0.05) for MFD treatment and lowest for CON, with FLD and WSD similar to both extremes. Dogs fed the MFD had the largest quantity (P < 0.05) of feces excreted and FLD the least. Dogs fed the FLD had highest (P < 0.05) overall nutrient digestibility values; whereas, MFD had the lowest values. TiO₂ estimates of fecal output correlated best to all other markers. The MFD had more than 2-fold (P < 0.05) the antioxidant value by ORAC versus the other treatments (20,482 vs average 8,923 μM Trolox Equivalent/L). This study suggests that sorghum flour would benefit easy-to-digest foods and the sorghum mill-feed could benefit foods needing indigestible fiber and antioxidants. Titanium dioxide may be a better marker for fecal output than Cr₂O₃ or TFC. Future work should determine the optimal mill-feed level to provide health benefits without affecting nutrient digestibility.
Keywords: sorghum; milling; extrusion; digestibility; antioxidantspetfood